2006
DOI: 10.1080/00071660600612324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phytoestrogens on testosterone secretion by Leydig cells from Biłgoraj ganders (Anser anser)

Abstract: The aim of this study was to examine ganders at different stages of the reproductive season and the effect of: (1) diets with high phytoestrogen content and (2) in vitro phytoestrogen treatment on testosterone secretion by isolated Leydig cells. Thirty-six male Biłgoraj geese were fed control diets with low phytoestrogen content (containing grass meal) and diets with high phytoestrogens (containing alfalfa meal and soy). Testes were obtained from both groups of ganders at three different times of the breeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 42 publications
2
25
1
3
Order By: Relevance
“…Histological and morphometric analyses revealed that gander testes undergo marked structural seasonal changes as it has been described in Bilgoraj goose (Anser anser) and Canadian goose (Branta canadensis) [28,31,32] and other bird species [1,20,25,42]. Interestingly, structural changes in testicular tissue in the sexual reactivation phase remain weakly researched, especially in geese.…”
Section: Discussionmentioning
confidence: 94%
“…Histological and morphometric analyses revealed that gander testes undergo marked structural seasonal changes as it has been described in Bilgoraj goose (Anser anser) and Canadian goose (Branta canadensis) [28,31,32] and other bird species [1,20,25,42]. Interestingly, structural changes in testicular tissue in the sexual reactivation phase remain weakly researched, especially in geese.…”
Section: Discussionmentioning
confidence: 94%
“…The activated AhR forms a heterodimer with AhR nuclear translocator protein (ARNT) and then binds to a xenobiotic responsive element in the promoter region of many genes of the so-called AhR gene battery for induction of transcription (Nebert et al, 2000). Phytoestrogens are natural compounds affecting sexual behavior as well as morphology and function of male and female reproductive organs (Opalka et al, 2006). Chansakaow et al (2000) identified deoxymiroestrol (DM) as the active component that found in Pueraria candollei tuber, a traditional Thai medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of total phytoestrogens in C and P diets were 15.40-40.44 and 118.54-151.19 µg/g, respectively. Detailed diets compositions and concentrations of phytoestrogens were previously described (Opałka et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Animals were kept and fed as previously described (Opałka et al, 2006). Briefl y, 1-day-old (April/May hatched) Biłgoraj male goslings (Anser anser) were divided into a control group fed diets containing low levels of phytoestrogens (C), based on grass meal and a group fed diets containing with higher levels of phytoestrogens (P), based on lucerne meal and soyabean meal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation